Influence of public agricultural extension services on sustainable land management practice adoption among smallholder farmers in Fetakgomo Tubatse Local Municipality, South Africa - Mugari, Ephias; Mathebula, Norman; Mogale, Tlou Elizabeth; Mamabolo, Emogine; Mashala, Makgabo Johanna; Mabitsela, Kabisheng; Ayisi, Kwabena Kingsley (Frontiers in Sustainable Food Systems, 2025)
IntroductionSustainable land management practices (SLMPs) are critical to combating land degradation and food insecurity while improving local economies. However, the role of public agricultural extension services in facilitating SLMP adoption in rural, developing country contexts remains poorly understood.MethodsThis study investigated the influence of public agricultural extension services on the adoption of SLMPs among smallholder farmers in four villages (Mphanama, Ga-Radingwana, Ga-Matlala, and Maseleseleng) in Fetakgomo Tubatse Local Municipality, South Africa. Cross-sectional data were collected from 242 randomly selected farming households using semi-structured questionnaires and key informant interviews. A recursive bivariate probit regression model (RBP) was employed to examine the endogenous relationship between extension access and SLMP implementation.ResultsContrary to expectations, the results revealed a significant negative influence of public extension services on SLMP implementation (p < 0.001). A perfect error correlation (p = 1) indicated that unobserved factors and systemic barriers jointly influenced extension access and SLMP implementation. While awareness of land degradation (p < 0.001) and formal employment (p = 0.007) strongly predict access to public extension services, SLMP implementation was primarily driven by access to irrigation (p < 0.001) and use of fertilizers (p = 0.015), with larger cropped areas discouraging SLMP implementation (p = 0.012).DiscussionThese results suggest public agricultural extension programs in the Mphanama area were misaligned with farmer needs or failed to address structural barriers like resource access. The findings underscore the need to transform traditional agricultural extension approaches by integrating digital and in-person advisory services while prioritizing localized knowledge. There is also a need for public agricultural extension services to extend beyond information dissemination to provide low-resource farmers with resources that reduce structural barriers while enhancing the effectiveness of extension services and the implementation of sustainable practices.ConclusionThis study demonstrates that access to public agricultural extension services alone is insufficient when broader systemic and structural constraints remain unresolved. Future research should integrate mixed methods and longitudinal designs and expand qualitative inquiry to explore the underlying social and institutional factors affecting extension access and SLMP adoption.